Crinkleroot's visit to Crinkle Cove - Arnosky, Jim. (New York : Simon & Schuster Books for Young Readers, 1998)
Crinkleroot searches for his friend, a small orange snake, through a soggy shoreland woods to the lake, under lily pads, and on a grassy knoll full of frogs, examining the animals and plants along the way.
"Ages 4-8"--cover p. [4].
Accelerated Reader AR
Keywords: Lake ecology -- Fiction; Ecology -- Fiction; Snakes -- Fiction